2013
DOI: 10.1212/wnl.0b013e3182918d38
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with statins and ischemic stroke severity

Abstract: Pretreatment with statins is associated with lower stroke severity, at high as well as at low to moderate doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…Interestingly, a recent study showed an association of pretreatment with statins and mild stroke severity on admission, which was pronounced in patients with high-dose statin therapy. 22 A part of the observed effects in our study might be explained by lower cholesterol levels in statin users. Lower cholesterol has been identified as a risk factor for ICH and has been linked to hemorrhagic transformation in the setting of thrombolysis.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Interestingly, a recent study showed an association of pretreatment with statins and mild stroke severity on admission, which was pronounced in patients with high-dose statin therapy. 22 A part of the observed effects in our study might be explained by lower cholesterol levels in statin users. Lower cholesterol has been identified as a risk factor for ICH and has been linked to hemorrhagic transformation in the setting of thrombolysis.…”
Section: Discussionmentioning
confidence: 67%
“…Patients were excluded for missing data about statin use or dose (n=6) or lacking information about sICH (n=3). The Berlin cohort consisted of 781 patients (median age, 75; median NIHSS score, 10; previous statin use, 22.4%; sICH rate, 3.9%; favorable outcome, 46.8%) and the Basel cohort consisted of 660 patients (median age, 74; median NIHSS score, 12; previous statin use, 21.4%; sICH rate, 3.3%; favorable outcome, 58.9%). Overall, the median age of the study population was 75 years, and the median NIHSS score was 11.…”
Section: Resultsmentioning
confidence: 99%
“…Even in hemorrhagic stroke data from recent studies suggest that statin therapy could improve the outcome after spontaneous intra-cerebral hemorrhage and statin therapy should be not discontinued [66][67][68][69]. Pre-treatment with statins is associated with lower stroke severity, at high as well as at low to moderate doses [70]. Other data suggest that we cannot draw any conclusion about the effectiveness and safety of lowering cholesterol in aneurismal SAH because insufficient reliable evidence from trials [71].…”
Section: Strokementioning
confidence: 99%
“…Because initial neurological severity is a significant determinant of functional outcome after ischemic stroke [6], it is also of clinical interest to determine whether pre-stroke statin management influences neurological severity and functional outcome after ischemic stroke. However, although accumulated evidence suggests that patients already receiving statins are at an advantage in terms of a reduced neurological severity after ischemic stroke because of the immediate beneficial effects of statins, the effect of pre-stroke statin treatment on initial stroke severity and on functional outcome remains controversial, even among studies performing systematic reviews and meta-analyses of previous results [7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Because most of the previous studies focused on the effect of pre-stroke statin treatment on functional outcome, potential confounding factors were not adjusted by multivariable analyses for the association between pre-stroke statin treatment and initial stroke severity [7,8,11,13,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Because most of the previous studies focused on the effect of pre-stroke statin treatment on functional outcome, potential confounding factors were not adjusted by multivariable analyses for the association between pre-stroke statin treatment and initial stroke severity [7,8,11,13,15,16,17]. Previous studies were also limited by a small sample size [7,8,9,11,12,14], a single center-based setting [9,12,13,16,17], or including patients with premorbid neurological dysfunction for the study participants [8,9,10,12,14,15,16], which may have contributed to the conflicting results.…”
Section: Introductionmentioning
confidence: 99%